State of the practice and engineering framework for using emergent vegetation in coastal infrastructure - Ostrow, Kayla; Guannel, Greg; Biondi, Esteban L.; Cox, Daniel T.; Tomiczek, Tori (Frontiers in Built Environment, 2022)
Natural and nature-based features are promoted as alternatives to structural flood protection measures. Progress has been made in understanding the physics and engineering of these systems; however, engineering, ecological, and social barriers to implementation remain. This paper identifies these barriers with a literature review and summary of expert opinion, contrasts the state of the practice of NNBF with traditional structures, and details the main engineering challenges to NNBF implementation, including the uncertainty in current calculation techniques and lack of engineering design guidelines. However, emergent vegetation systems can be designed with the current body of information, and an example framework is proposed for assessing these systems for their wave attenuation performance. The framework is discussed in the context of risk, and future research priorities are presented.